Effect of Heating Rate and Temperature on the Carbonization Process of Commercial Viscose fibers - Nguyen, Huu Son; Vu, Le Hoang; Pham, Van Cuong; Le, Thai Hung (Old Journal, 2018)
Effect of heating rate and temperature on the carbonization process of commercial Viscose (cellulosic based precursor) fibers are investigated in the present study. Several carbonization experiments are conducted on stabilized fibers with carbon content of 59.72 wt% and diameter of about 13.3 μm. The Viscose fibers are stabilized with the catalyst of mixture urea/diammonium hydrogen phosphate in air at temperature of 250 °C. The stabilized fibers are then carbonized in argon at temperature ranging from 600 °C to 1200 °C with the heating rate of 5 °C·min⁻¹. Experimental results show that the obtained fibers have carbon content above 94 wt% and diameters of about 8μm. These fibers are potential to produce activated carbon fibers.